Ondansetron and Granisetron for Prevention of Postoperative Nausea and Vomiting following Laparoscopic Cholecystectomy - Sabin Gauchan; Chitra Thapa; Priyanka Shakya; Ramesh Bhattarai; Sajal Shakya (Journal of Nepal Medical Association, 2014)
Introduction: Laparoscopic surgeries are known to be associated with a higher incidence of postoperative nausea and vomiting. Prophylaxis of PONV is usually achieved with a single-dose antiemetic drug administered during the surgical procedure. The aim of this study was to compare the antiemetic efficacy of two different 5-hydroxytryptamine-3 receptor antagonists, ondansetron and granisetron when given prophylactically to patients undergoing laparoscopic cholecystectomy.